Influences of international trade policy and the COVID-19 Pandemic on fishery industry: an example of the Taiwan hairtail industry - Ching-Hsien Ho; Yu-Cing Ma; Chi-Chang Lai (Discover Sustainability)
Abstract Sustainability in fisheries is critical to the global food supply, making the study of fishery industries essential. Taiwan's hairtail fishery represents a significant component of the nation’s fishing industry, offering valuable insights into broader trends and challenges. This study aims to examine the influences of changes in trade policy and trade conditions (COVID-19 pandemic) using the hairtail industry in Taiwan as an example, providing insights into how external shocks, such as global health crises and policy reforms, affect the fisheries sector, particularly in regions reliant on small-scale or traditional fishing practices. The findings indicate that hairtail productions and prices remained stable between 2012 and 2015. However, increasing demand and export opportunities in China drove significant growth in production and market prices from 2016 to 2019. This upward trend was abruptly disrupted in 2020 by the COVID-19 pandemic, which caused a sharp decline in production and prices. The return of unsold products from the Chinese market to the local market further suppressed prices, highlighting the vulnerability of the industry to external shocks. Digitalization played a crucial role during this period, facilitating the even redistribution of products in domestic markets, stabilizing prices, and reducing losses. Looking forward, further digitalization is essential to enhance the resilience of the hairtail fishery. Advanced digital tools will not only strengthen the industry's ability to adapt to future disruptions but also ensure traceability, meeting the demands of international trade and fostering sustainable growth.